A new strategy for accessing (S)-1-(furan-2-yl)pent-4-en-1-ol: a key precursor of Ipomoeassin family of compounds and C1–C15 domain of halichondrins. Issue 35 (31st August 2016) - Jammula, Subba Rao; Anna, Venkateswara Rao; Tatina, Sudhakar; Krishna, Thalishetti; Sreenivas, B. Yogi; Pal, Manojit
Graphical abstract: Highlights: A practical synthesis of ( S )-1-(furan-2-yl)pent-4-en-1-ol has been achieved. The methodology does not require resolution of enantiomers. The overall yield (i.e. 75%) is better than that (i.e. ∼42%) of an earlier method. The title compound was converted to a promising cytotoxic agent. Abstract: A highly efficient synthesis of ( S )-1-(furan-2-yl)pent-4-en-1-ol, known to be an initial precursor of Ipomoeassin family of compounds and C1–C15 domain of halichondrins has been achieved via a sequence involving the use of Weinreb amide formation followed by Weinreb ketone synthesis and finally CBS (Corey–Bakshi–Shibata) reduction. Detailed study on improvement of each step is described. The title compound was converted to a potential cytotoxic agent for further pharmacological studies.